2006
DOI: 10.1080/08916930600738383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standard nicotinamide in the prevention of type 1 diabetes in first degree relatives of persons with type 1 diabetes

Abstract: Type 1 diabetes prevention trial using standard nicotinamide is feasible but fails to prevent or delay the disease onset at the dose we used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Thus, oral NAM administration is thought to be a therapeutic agent for T1DM. Although small-scale clinical trials have reported the beneficial effects of NAM against T1DM [76], a large-scale randomized controlled trial demonstrated that NAM intervention in patients with confirmed anti-islet cell antibodies failed to prevent the onset of T1DM [77]. For T1DM treatment, NMN and NR are still attractive candidates because NAD-mediated SIRT1 activation augments GSIS in β-cells [78].…”
Section: Diabetesmentioning
confidence: 99%
“…Thus, oral NAM administration is thought to be a therapeutic agent for T1DM. Although small-scale clinical trials have reported the beneficial effects of NAM against T1DM [76], a large-scale randomized controlled trial demonstrated that NAM intervention in patients with confirmed anti-islet cell antibodies failed to prevent the onset of T1DM [77]. For T1DM treatment, NMN and NR are still attractive candidates because NAD-mediated SIRT1 activation augments GSIS in β-cells [78].…”
Section: Diabetesmentioning
confidence: 99%
“…NAM treatment induced liver NAD + levels, which were complimented by enhanced glucose control (Yang et al, 2014). Despite NAM being suggested as a treatment for type 1 diabetes (Olmos et al, 2006), clinical trials failed to confirm this hypothesis (Cabrera-Rode et al, 2006; Gale, Bingley, Emmett, Collier, & European Nicotinamide Diabetes Intervention Trial (ENDIT) Group, 2004).…”
Section: The Choice Of Nad+ Precursor Is Criticalmentioning
confidence: 99%
“…However, long-term NAM treatment increases NAD + levels via the NAD + salvage pathway, which likely tips the balance of the NAD + /NAM ratio such that SIRT1 is activated. Despite NAM being suggested as a treatment for type 1 diabetes (Olmos et al, 2006), clinical trials failed to confirm this hypothesis (Cabrera-Rode et al, 2006; Gale et al, 2004). More recently OLETF rats, a rodent model of obesity and type 2 diabetes, exhibited profound metabolic improvements following NAM treatment (100mg/kg for 4 weeks).…”
Section: Introductionmentioning
confidence: 99%